2021
DOI: 10.5603/cj.a2021.0072
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of effect of vitamin D levels on the incidence of COVID-19

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 54 publications
3
38
0
4
Order By: Relevance
“…Vitamin D3 metabolism was predicted to be down-regulated in one dataset by GIMME models, and in all by tINIT models. This is in line with several meta-analyses of published data, which found significantly lower 25(OH)D concentration, and significant relation between the low concentration and infection, severity or mortality of COVID-19 patients [ [61] , [62] , [63] , [64] , [65] , [66] ]. Vitamin D3 supplementation has been hypothesised to affect clinical outcomes in patients with COVID-19, however; this was not successfully confirmed [ 61 , 67 ].…”
Section: Discussionsupporting
confidence: 90%
“…Vitamin D3 metabolism was predicted to be down-regulated in one dataset by GIMME models, and in all by tINIT models. This is in line with several meta-analyses of published data, which found significantly lower 25(OH)D concentration, and significant relation between the low concentration and infection, severity or mortality of COVID-19 patients [ [61] , [62] , [63] , [64] , [65] , [66] ]. Vitamin D3 supplementation has been hypothesised to affect clinical outcomes in patients with COVID-19, however; this was not successfully confirmed [ 61 , 67 ].…”
Section: Discussionsupporting
confidence: 90%
“…Although most heated discussions revolve around vitamin D, other dietary supplements have also been administrated by clinicians in an off-label basis, thanks to their broad role in immune system function and minimal adverse effect burden. Vitamin C [ 41 ] and zinc [ 42 ] offered no benefit regarding disease outcomes. Vitamin B12, which was co-administered with vitamin D and magnesium in one of our included studies, might facilitate symptom alleviation in COVID-19 [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…As far as COVID-19 is concerned, vitamin D status is regularly proven to attain a prognostic value in large recent meta-analyses. Lower vitamin D levels are measured in COVID-19 patients than in healthy individuals [ 42 , 48 ], indicating a possible link with susceptibility to infection. Indeed, vitamin D deficiency increased the odds of contracting SARS-CoV-2 by 80% [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, its use has been proposed in the initial phase of SARS-CoV-2 associated pandemic, since March 2020, with preventive or therapeutic purpose in patients with COVID-19 at higher risk of developing severe forms of diseases, such as aged people or immunocompromised individuals ( Fiorino et al, 2020 , 2021a ). Several meta-analyses have confirmed these preliminary suggestions and have reported that individuals with vitamin D deficiency are at higher risk of SARS-CoV-2 infections and of a poorer clinical outcome in comparison with subjects with normal levels of this micronutrient ( Kaya et al, 2021 ; Ghasemian et al, 2021 ; Szarpak et al, 2021 ; Oscanoa et al, 2021 ), whereas only a few studies have examined the effects of vitamin D supplementation in patients suffering from COVID-19. Although these investigations have shown interesting results, the number of enrolled individuals is small.…”
Section: Discussionmentioning
confidence: 91%